Evaluations for sustainable forest management: towards an adaptive standard for the evaluation of the ecological sustainability of forest management in Costa Rica - McGinley, K.; Finegan, B. (Centro Agronómico Tropical de Investigación y Enseñanza, 2002)
The research was carried out with the general objectives of contributing to the definition of sustainable forest management in the region of Central America, determining guidelines for the ecological sustainability of forest management that include elements for adaptive management and developing principle, criteria, indicators & verifiers (PCI&V) for its reliable and efficient evaluation in Costa Rica. The process began with an initial set of PCI&V comprised of elements from the national standard for forest management in Costa Rica and the CIFOR generic template of C & I for adaptive management. The first phase consisted of office evaluations on the relative importance and priority of the initial set of PCI&V by a group of expert in forest management and ecology. The second phase, which served as a filter through which each element was either recommended, modified or rejected for the final set of PCI&V, included testing and evaluation of the initial set of PCI&V by expert group. The third and final phase consisted of a workshop with a larger group of experts in forest management, ecology and policy in which the results were presented and approved. The distribution of institutional responsibility associated with the implementation of the recommended elements was also discussed and evaluated.